Chemicals used for maintenance of wood rafts in mussel farms: evaluation of their potential toxic risk to mussel culture - Y Ruiz (Inter-Research, 2014)
At the Galician coast, mussels are cultured on vertical ropes attached to floating rafts, which are cleaned in situ with tars or waterproof paints. The present study analyses the composition and the toxic risk of several compounds used during maintenance, in order to improve mussel-farming practices. The toxic risk was determined in relation to that of benzo(a)pyrene (BaP) by calculating the carcinogenic toxic equivalency (TEQ) and evaluating the mutagenic potential using a mutagenicity test based on Vibrio harveyi. The greatest toxic risk was determined for a random mixture of petroleum tars and diesel combusted oil (MTO). This mixture showed a concentration of polycyclic aromatic hydrocarbons 200-fold higher than that of coal tar (CT) and 256-fold higher than pine tar (PT) as well as significantly higher concentrations of Pb and Mn. The TEQ value of MTO was 581-fold and 486-fold higher than that of the CT and PT, respectively. In the waterproof paint (WP) analysed, hydrocarbons were not detected, but the Mn, Cr, Cu, Sn, and Ni content of the WP was significantly higher than that of the tars. Mutagenicity of the tars was dose-dependent and increased after metabolic activation. The MTO showed mutagenic effects that were significantly higher than those of CT and PT but still less than expected, suggesting that the mutagenic potential of all 3 mixtures depends on their concentration and composition, which determine their solubility and biodegradability. The WP did not show mutagenic effects. Our results suggest that the use of WP and PT is more suitable for the maintenance of rafts and could reduce the pollutant impact in the mussel farms.